2019
DOI: 10.17159/2520-9868/i76a03
|View full text |Cite
|
Sign up to set email alerts
|

Improving Grade R mathematics teaching in South Africa: Evidence from an impact evaluation of a province-wide intervention

Abstract: We present the impact on learner outcomes of a province-wide Grade R mathematics intervention (termed R-Maths) in relation to theoretical frameworks established from a meta-evaluation of evaluations of education interventions in South Africa and a review of other meta-evaluation and synthesis studies. We compare the changes in Mathematics performance from baseline to end line, of learners in the intervention group (taught by R-Maths-trained teachers/practitioners) to the comparison group (learners in schools i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The analysis of the results of the Foundations of Learning Campaign revealed that the campaign did not focus on the alternative pedagogical approaches; instead teachers were merely given material. Research continued to point at the inconsistencies in the pedagogical approaches, emanating from the unaligned and uninformed practices in mathematics classrooms nationally (Hazell, Spencer & Robert, 2019;Henning et al (2019). In the same, vein (Graven, 2014) agreed that the campaign did not yield positive results to implement alternative pedagogical approaches for teaching and learning of mathematics in elementary classes.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the results of the Foundations of Learning Campaign revealed that the campaign did not focus on the alternative pedagogical approaches; instead teachers were merely given material. Research continued to point at the inconsistencies in the pedagogical approaches, emanating from the unaligned and uninformed practices in mathematics classrooms nationally (Hazell, Spencer & Robert, 2019;Henning et al (2019). In the same, vein (Graven, 2014) agreed that the campaign did not yield positive results to implement alternative pedagogical approaches for teaching and learning of mathematics in elementary classes.…”
Section: Introductionmentioning
confidence: 99%